1994
DOI: 10.1192/bjp.165.2.222
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Training Community Psychiatric Nurses to Deliver Psychosocial Intervention

Abstract: The study offers some evidence that CPNs can be taught to improve the outcome for families who care for a relative with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 19 publications
2
94
0
7
Order By: Relevance
“…If training and supervision are inadequate, such therapies are less likely to be effective (Fadden, 1998). Thorn training courses, run at centres in London, Manchester and Nottingham, have been shown to improve nurses' effectiveness in delivering researchbased interventions in schizophrenia (Brooker et al, 1994). Joint case discussions and team-based journal clubs on evidence-based practice can enable interprofessional sharing of complementary perspectives and promote continuing professional development.…”
Section: Developing and Maintaining Core Skillsmentioning
confidence: 99%
“…If training and supervision are inadequate, such therapies are less likely to be effective (Fadden, 1998). Thorn training courses, run at centres in London, Manchester and Nottingham, have been shown to improve nurses' effectiveness in delivering researchbased interventions in schizophrenia (Brooker et al, 1994). Joint case discussions and team-based journal clubs on evidence-based practice can enable interprofessional sharing of complementary perspectives and promote continuing professional development.…”
Section: Developing and Maintaining Core Skillsmentioning
confidence: 99%
“…These studies have reported positive effects of family intervention, including reduced relapse or rehospitalization, along with improved occupational functioning, social functioning, and family burden. In addition, Brooker et al (1994) conducted a quasi-experimental study to evaluate the effects of training community nurses in behavioral family therapy (based on Falloon et al's, 1984, model). In a within-subjects design, families were placed on a waiting list for 6 months, followed by 12 months of family intervention, or assigned to a delayed treatment group for whom family treatment was initiated 1 year later.…”
Section: Effectivenessmentioning
confidence: 99%
“…In una revisione relativamente recente, Lehman et al (1995) riportavano lo scarso aggiornamento degli operatori dei servizi psichiatrici nell'applicazione persino delle strategic farmacologiche piii elementari e la totale mancanza di applicazione delle strategie psicosociali. Lo studio di Brooker et al (1994) ha mostrato che il tempo che ogni infermiere psichiatrico territoriale dedicava agli utenti afferenti al servizio era di 33 minuti settimanali per la conduzione di approcci non-specifici e che invece erano necessari 47 minuti per condurre un intervento psicosociale integrato con gli utenti ed i loro familiari. Questi ultimi interventi producevano, ad un anno, un netto miglioramento della sintomatologia e del funzionamento sociale della persona, con una netta riduzione delle giornate di ricovero, mostrando una riduzione statisticamente significativa del disagio dei familiari, una loro maggior conoscenza dei farmaci antipsicotici ed una loro maggior soddisfazione nei confronti del servizio (Brooker et al, 1994).…”
Section: La Diffusione Dei Trattamenti Psicoeducativi Familiariunclassified
“…Lo studio di Brooker et al (1994) ha mostrato che il tempo che ogni infermiere psichiatrico territoriale dedicava agli utenti afferenti al servizio era di 33 minuti settimanali per la conduzione di approcci non-specifici e che invece erano necessari 47 minuti per condurre un intervento psicosociale integrato con gli utenti ed i loro familiari. Questi ultimi interventi producevano, ad un anno, un netto miglioramento della sintomatologia e del funzionamento sociale della persona, con una netta riduzione delle giornate di ricovero, mostrando una riduzione statisticamente significativa del disagio dei familiari, una loro maggior conoscenza dei farmaci antipsicotici ed una loro maggior soddisfazione nei confronti del servizio (Brooker et al, 1994). Tali risultati dovrebbero ulteriormente incoraggiare gli investimenti interni di formazione sugli interventi psicosociali efficaci: Putilizzazione di pacchetti specifici di insegnamento e di materiali strutturati nella conduzione degli interventi facilitano una buona riproducibilita e la verifica di processo, oltre che di esito, dei trattamenti.…”
Section: La Diffusione Dei Trattamenti Psicoeducativi Familiariunclassified